COVID-19 Pandemic – A Testing Time for Tourism and Hospitality in Thailand - Vithayaporn, Sanhakot (ABAC ODI JOURNAL Vision. Action. Outcome, 2021)
The COVID-19 pandemic has recently led to a global alarm due to its fatal nature from the spread of the coronavirus. Thailand is currently aware of this unprecedented time and the Thai cabinet has imposed a state of emergency to prevent the spread of this virus. The tourism and hospitality sectors have been devastated by the coronavirus. Therefore, the purpose of this study aims to examine the impact on tourism and hospitality including airline and hotel sectors. The study used adopt secondary data from various sources both academic and practitioner as critical discourse analysis for textual analysis and synthesis. Data were obtained from fifty articles discussed in this paper. The paper indicates the impact of the pandemic on tourism, airline and hotel sectors. Moreover, results are also highlighted negative impact on Thailand tourism and hospitality industry from the crisis by proven the decreased number of international tourist arrival. The implementation of social protection, and government aid policy to support people affected by the pandemic is also are presented in the result of this study. In conclusion and implication, this research/paper will further help the industries to take initiative strategies and best policies to be implemented in the future to combat the disease. Future research is also recommended in this study.